PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI - Francisco Soares de Jesus; Nurdjanah Hamid; Maat Pono (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
The university is one of the containers, where the provision of service facilities and provide human resource capacity to the identical community of various sciences. This study aims to determine to know the influence of Organizational Culture, Leadership Style and Organizational Commitment in improving job performance Employees consisting of permanent and non permanent lecturer at Unpad Unpad Dili Timor-Leste. The type of research used in this study is quantitative approach. The quantitative approach is based on the approach done by recording and analyzing the data of the research results by using statistical calculations supported by literature study and data collection tool in the form of questionnaires distributed to permanent and non permanent lecturers at Unpad Unpad Dili Timor-Leste. The results showed that partially organizational culture, positive and significant effect on employee performance, leadership style has a positive and significant impact on employee performance, as well as organizational commitment have a positive and significant impact on employee performance.